Effects of Foliar Application of Salicylic Acid On Morphological, Biochemical and Yield Attributes of Maize (Zea Mays L.) Under Rainfed Condition (Bangladesh Journal of Botany, 2024)
An experiment was performed in the kharif- 2022 focusing on the impact of foliar applications of Salicylic acid on various morphological, biochemical, and yield attributes in maize, using the CP-858 variety. The study involved four concentrations of salicylic acid: T1-50ppm, T2-100ppm, T3-150ppm, and T4-175ppm. Notable differences emerged in morphological and yield attributes such as sink size, test weight and yield per plot, revealing a marked increase in plant physiological efficiency treated with Salicylic acid when compared to the control. This trend was also evident in key biochemical parameters like chlorophyll 'a', 'b', and total chlorophyll content, and protein content in leaves, showing a positive response to exogenously applied Salicylic acid. Similar outcomes were recorded in terms of yield and yield-related indicators. These outcomes underscore the significance of Salicylic acid as a potent growth regulator for crop plants, particularly those cultivated under dryland conditions.Bangladesh J. Bot. 53(2): 273-278, 2024 (June)